Radical scavenging capacity of Piper arboreum and Piper tuberculatum (Piperaceae) - Regasini, Luis O. [UNESP]; Cotinguiba, Fernando [UNESP]; Siqueira, Janaina R. [UNESP]; Bolzani, Vanderlan S. [UNESP]; Silva, Dulce H.S. [UNESP]; Furlan, Maysa [UNESP]; Kato, Massuo J. (My University, 2008)
In the scope of our ongoing researchers on antioxidant compounds, twenty four extracts and fractions obtained from Piper arboreum Aublet and Piper tuberculatum Jacq. (Piperaceae) were screened for radical scavenging capacity (RSC) by using DPPH colorimetric assay. The strongest activity was found in ethyl acetate fractions from the leaves of P. arboreum (IC50 = 5.70 μg/mL) and P. tuberculatum (IC50 = 8.40 μg/mL). Hydromethanol fractions of the leaves of P. tuberculatum and P. arboreum showed moderate RSC, with values of IC50 (μg/mL) of 11.9 and 19.2, respectively. Additionally, a brief phytochemical study of the ethyl acetate fraction of P. arboreum leaves affording quercetin (1) and quercitrin (2), two flavonols with antioxidant activity previously described in the literature.
Keywords: Antioxidant; DPPH; Piper arboreum; Piper tuberculatum; Piperaceae; Radical Scavenging Capacity